1983
DOI: 10.1080/00913847.1983.11708703
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal and Cardiopulmonary Characteristics of the Professional Ballet Dancer

Abstract: In brief: Sixteen professional ballet dancers from the Ohio Ballet in Akron were x-rayed, tested on a Cybex dynamometer, and tested for maximal aerobic power on a treadmill to determine musculoskeletal and cardiopulmonary capabilities. The x-rays indicated that the dancers had metatarsal abnormalities characteristic of such artists. The Cybex data were considered normal for the knee. The dancers had higher than normal cardiopulmonary capacity, although it was still in the range of nonendurance athletes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
1
2

Year Published

1984
1984
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 12 publications
3
20
1
2
Order By: Relevance
“…This produces VO 2max values within the range of non-endurance athletes. 89,91,92,[94][95][96][97] A recent study of university and professional dancers found physiological responses to modern dance class appear to mimic those of classical ballet class. 93 There were significant differences between modern dance class and performance in VO 2 , heart rate, and work.…”
Section: Aerobic Conditioningmentioning
confidence: 99%
“…This produces VO 2max values within the range of non-endurance athletes. 89,91,92,[94][95][96][97] A recent study of university and professional dancers found physiological responses to modern dance class appear to mimic those of classical ballet class. 93 There were significant differences between modern dance class and performance in VO 2 , heart rate, and work.…”
Section: Aerobic Conditioningmentioning
confidence: 99%
“…Physiological profiling of dancers is not new; Cohen et al 2 and Mostardi et al 3 used treadmill-running protocols to measure maximal aerobic power in ballet dancers, whereas Rimmer et al 4 used a walking profile, but again, on a treadmill. Clarkson et al 5 investigated maximal oxygen uptake in adolescent female ballet dancers, again using a treadmill protocol.…”
mentioning
confidence: 99%
“…These results may be due in part to the specific nature of the types of dance that were observed, whose movement sequences, although dynamic, can be considered short-lasting with energy provided by the phosphagen (ATP and phosphocreatine) and anaerobic (glycolytic) systems. In these studies, rarely was research conducted on motion sequences lasting for a few minutes or longer [9,14]. Although dancing involves the same large muscle groups, the energy pathways that are involved can differ depending on dance style, intensity, technique, and duration.…”
Section: Introductionmentioning
confidence: 99%
“…Previously published data on the levels of physical fitness of dancers and the physiological response during dancing focused mainly on modern and ballroom dancing, ballet, and aerobic dance workouts [3][4][5][6][7][8][9][10][11][12][13]. These studies found that the aerobic fitness level of dancers can be considered as average and characteristic of individuals practicing non-endurance sports [3,5,9,13]. These results may be due in part to the specific nature of the types of dance that were observed, whose movement sequences, although dynamic, can be considered short-lasting with energy provided by the phosphagen (ATP and phosphocreatine) and anaerobic (glycolytic) systems.…”
Section: Introductionmentioning
confidence: 99%